An intervention designed to improve sensory impairments in the elderly and indoor lighting in their homes: an exploratory randomized controlled trial [Corrigendum] - Haanes GG; Kirkevold M; Hofoss D; Horgen G; Eilertsen G (Journal of Multidisciplinary Healthcare, 2015)
Haanes GG, Kirkevold M, Hofoss D, Horgen G, Eilertsen G. J Multidiscip Healthc. 2015;8:11–20.On page 15, Visual status heading, the first sentence “The results from the vision test are presented in Table 3” should have been removed from the paper. Read the original paper